Features Of the Organization of Extraordinary Physical and Health and Public Events in General Secondary Educational Institutions (Eurasian Research Bulletin, 2022)
In this article, teachers of physical culture of educational institutions need to obtain theoretical knowledge on the organization and conduct of extracurricular sports and recreation and sports events at a high level and apply them in practice and advance in their field. Professional knowledge, skills and abilities necessary for the acquisition and implementation of experience, modern knowledge and skills, as well as the development of their creative activity.